DIVERSITY OF LAND ARTHROPODA ON PEOPLE’S PLANTATIONS AT JAWATONGAH VILLAGE, HATONDUHAN SUB-DISTRICT IN SIMALUNGUN NORTH SUMATERA - Gunaria Siagian (JBIO: jurnal biosains (the journal of biosciences), 2020)
This study aims to determine the diversity, abundance, dominance index, similarity index and inequality of land arthropods in the people's plantations in the village of Jawatongah, Hatonduhan Subdistrict, Simalungun Regency. This research was conducted in October 2019 until November 2019. Sampling was carried out at 5 stations in the People's plantation in Jawatongah Village, Hatonduhan District, Simalungun Regency. Data retrieval is done 3 times using trap traps. From the results of research and data analysis found 9 orders and 1 family consisting of 9 orders and 16 families consisting of: Formicidae, Flatidae, Silphidae, Anobiidae, Labiduridae, Tephritidae, Culicidae, Rhagionidae, Simuliidae, Blephariceridae, Gryllidae, Anobiidae, Labiduridae, Tephritidae, Culicidae, Rhagionidae, Simuliidae, Blephariceridae, Gryllidae, Anobiidae, Labiduridae, Tephritidae, Culicidae, Rhagionidae, Simuliidae, Blephariceridae, Gryllidae, Acobiidae, Acrididae, Phrididae, Acrididae, Acrididae, Acrididae, Acrididae, Acrididae, Acrididae, Acrididae, Acrididae, Acrididae, Acrididae, Acrididae, Acrididae, Acrididae. Lachesillidae, Liposcelidae, Pholidae, Araneidae, Ageleidae. The highest relative abundance of soil Arthropods was Tephritidae (71, 486%), the lowest was Liposcelidae and Aranidae (0.367%). The diversity index of the Athropods of the soil ranged from 0.996-1.536. The dominance index ranged from 0, 27155 - 0.53598. From these observations it can be seen that in general the Tephritidae group dominates all places in the study location. For the Arthropod similarity index of land in the smallholder plantations of Jawatongah village, Hatonduhan sub-district, Simalungun Regency, ranged between 55.56% - 80%. Knowledge and knowledge about diversity, abundance, status and distribution of animals are very important for humans and need to be preserved to improve the welfare of society, especially in agriculture.